Diagnosis of multiple sclerosis: progress and challenges - Brownlee, Wallace J; Hardy, Todd A; Fazekas, Franz; Miller, David H (The Lancet (British edition), 2017)
The diagnosis of multiple sclerosis is based on neurological symptoms and signs, alongside evidence of dissemination of CNS lesions in space and time. MRI is often sufficient to confirm the diagnosis when characteristic lesions accompany a typical clinical syndrome, but in some patients, further supportive information is obtained from cerebrospinal fluid examination and neurophysiological testing. Differentiation is important from other diseases in which demyelination is a feature (eg, neuromyelitis optica spectrum disorder and acute disseminated encephalomyelitis) and from non-demyelinating disorders such as chronic small vessel disease and other inflammatory, granulomatous, infective, metabolic, and genetic causes that can mimic multiple sclerosis. Advances in MRI and serological and genetic testing have greatly increased accuracy in distinguishing multiple sclerosis from these disorders, but misdiagnosis can occur. In this Series paper we explore the progress and challenges in the diagnosis of multiple sclerosis with reference to diagnostic criteria, important differential diagnoses, controversies and uncertainties, and future prospects.